The Role of Session Zero in Successful Completion of Chronic Disease Self-Management Program Workshops - Jiang, Luohua; Smith, Matthew Lee; Chen, Shuai; Ahn, SangNam; Kulinski, Kristie P.; Lorig, Kate; Ory, Marcia G. (Frontiers in Public Health, 2015)
.